Pertanggungjawaban Pelaku Tindak Pidana Lalu Lintas Yang Menyebabkan Korban Meninggal Dunia Akibat Kelalaian - Muhammad Ridwan Lubis (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Smooth traffic will bring smoothness in all efforts; otherwise, if traffic cannot create smoothness and regularity well, it causes many congestion and accidents which may influence to all social life. In writing this thesis, the author applies the method of literature review (library research) to examine secondary data and field research by doing research in the District Court Class I Medan and Medan Police. The factors affecting the increase of traffic accidents on the highways are caused by people’s lack of awareness and adherence to obey any traffic regulations. People always blame law enforcement officers (police) without realizing and filtering their own mistakes first. Indeed, to create the military and regularity in the traffic there must be a good cooperation between law enforcement officers and the people because without intertwining between the rights and obligations of law of the enforcement officers and the public, it is impossible to create tranquility, order and comfort in traffic. Such traffic accidents have happened since years ago and always increase up to now in Indonesia.